2000
DOI: 10.1002/1521-4141(200006)30:6<1638::aid-immu1638>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-derived long peptide immunotherapy down-regulates specific IgE response and protects from anaphylaxis

Abstract: To evaluate a long peptide‐based allergy vaccine in a murine model, CBA/J mice were sensitized with low dose alum‐adsorbed phospholipase A2 (PLA2), a major bee venom allergen. Presensitized mice were treated by daily i.p. injections of a mixture of three long overlapping peptides (44‐ to 60‐mer) spanning the entire PLA2 molecule (100 μ g/peptide) for 6 consecutive days. This therapeutic approach induced a sharp drop in PLA2‐specific IgE, an increase in specific IgG2a, and a marked T cell hyporesponsiveness. T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 22 publications
1
37
1
Order By: Relevance
“…However, SIT is time consuming, costly and bears the risk of allergic side effects. The latter can be reduced by pretreatment with anti-histamines [27,28], or by the use of allergen-derived peptides [17][18][19], chemically modified allergens [29,30] or recombinant allergens [11][12][13]31] with a reduced capacity to bind IgE. For instance, by producing fusion proteins of major allergens, one aim was to reduce IgE binding and therefore the allergic side effects, while yet retaining the immunotherapeutic potential due to preserved T cell epitopes, changes in protein folding and relative exposure of B cell epitopes [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SIT is time consuming, costly and bears the risk of allergic side effects. The latter can be reduced by pretreatment with anti-histamines [27,28], or by the use of allergen-derived peptides [17][18][19], chemically modified allergens [29,30] or recombinant allergens [11][12][13]31] with a reduced capacity to bind IgE. For instance, by producing fusion proteins of major allergens, one aim was to reduce IgE binding and therefore the allergic side effects, while yet retaining the immunotherapeutic potential due to preserved T cell epitopes, changes in protein folding and relative exposure of B cell epitopes [9].…”
Section: Discussionmentioning
confidence: 99%
“…For the same reasons, short, synthetic peptide sequences corresponding to T cell epitopes from the allergen have been used for SIT. This approach was able to modify surrogate markers of allergy including cutaneous responses to allergen challenge and ex vivo parameters of T cell activation [17][18][19]. Finally, chemical crosslinking of allergens by use of bi-functional aldehydes to produce so-called allergoids [20] has been shown to reduce reactogenicity with IgE while yet improving antigen processing, Th1 cytokine secretion, and efficacy [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…SIT is a burdensome procedure requiring 3-5 years of treatment and has to be conducted under medical supervision because it causes undesirable side effects in 15% of patients (4). In addition to modulating Ig production, SIT operates by decreasing both Ag-specific T cell proliferation (5-7) and IL-4 secretion (8), as well as triggering the prototype Th1 cytokine IFN-␥ (9,10).…”
Section: S Pecific Ag Immunotherapy (Sit)mentioning
confidence: 99%
“…In addition to immunotherapy with short synthetic peptides (11), large recombinant allergen fragment (12), and long synthetic peptides (9,10), gene vaccination appears as a safe and inexpensive alternative to classical immunotherapy (13). Recent findings by several laboratories have shown that immunization with DNA vectors encoding human allergens triggers a strong Th1 response to these allergens in rats and mice (14 -17).…”
Section: S Pecific Ag Immunotherapy (Sit)mentioning
confidence: 99%
“…Our previous experience with synthesis of long polypeptides (Ͼ100 amino acids) showed that we could produce good-manufacturing-procedure material quickly and efficiently for clinical studies (13,28). Long synthetic peptides (LSP) have been shown to be safe and immunogenic in preclinical (2,5,26,27,36,44) and clinical (20,28,45) trials and, therefore, should be considered good candidates for a phase I trial.…”
mentioning
confidence: 99%